(untitled) (KYAMC Journal, 2020)
Background: Multiple Myeloma (MM) represents approximately 15% of all hematological malignancies. Despite the use of high-dose chemotherapy followed by stem cell rescue MM remains incurable at present. The goal is to control the disease as much as possible, providing the best quality of life to patients for the longest duration. Currently, CTDa (attenuated Cyclophosphamide, Thalidomide, Dexamethasone) is the best option of treatment as it is cost-effective, with no need for hospitalization with a good response. Objective: To find out the symptomatic responses and toxicities of CTDa in Multiple Myeloma patients. Materials and Methods: 25 patients of newly diagnosed MM patients were treated in the Haematology Department, Bangabandhu Sheikh Mujib Medical University (BSMMU) from July 2016 to July 2017. The mean age of the patients was 54 years, Male female ratio was 1.5:1 and most of the patients were farmers. After induction of 4 to 6 cycles of CTDa all patients were followed up at 6th and 12th weeks. At follow up we evaluated improvement of weakness, bone pain, Hb%, ESR, monoclonal protein, ß2microglobulin, bone marrow plasma cells and serum calcium and albumin level. Adverse effects, such as peripheral neuropathy, thromboembolic events, hyperglycemia, constipation, rash, and somnolence were also assessed. Results: Among 25 patients, complete response achieved only 13 patients (52%), where 20% and 16% of patients belonged to partial or no response respectively. The death occurred in 2 cases (12%). Conclusion: CTDa is a gentle approach to treat an especially frail group of patients, since virtually all patients ultimately relapse. KYAMC Journal Vol. 11, No.-3, October 2020, Page 124-128